The functional evolution of termite gut microbiota - Arora, Jigyasa; Kinjo, Yukihiro; Šobotník, Jan; Buček, Aleš; Clitheroe, Crystal; Stiblik, Petr; Roisin, Yves; Žifčáková, Lucia; Park, Yung Chul; Kim, Ki Yoon; Sillam-Dussès, David; Hervé, Vincent; et al. (Microbiome, 2022)
BACKGROUND: Termites primarily feed on lignocellulose or soil in association with specific gut microbes. The functioning of the termite gut microbiota is partly understood in a handful of wood-feeding pest species but remains largely unknown in other taxa. We intend to fill this gap and provide a global understanding of the functional evolution of termite gut microbiota. RESULTS: We sequenced the gut metagenomes of 145 samples representative of the termite diversity. We show that the prokaryotic fraction of the gut microbiota of all termites possesses similar genes for carbohydrate and nitrogen metabolisms, in proportions varying with termite phylogenetic position and diet. The presence of a conserved set of gut prokaryotic genes implies that essential nutritional functions were present in the ancestor of modern termites. Furthermore, the abundance of these genes largely correlated with the host phylogeny. Finally, we found that the adaptation to a diet of soil by some termite lineages was accompanied by a change in the stoichiometry of genes involved in important nutritional functions rather than by the acquisition of new genes and pathways. CONCLUSIONS: Our results reveal that the composition and function of termite gut prokaryotic communities have been remarkably conserved since termites first appeared ~ 150 million years ago. Therefore, the "world's smallest bioreactor" has been operating as a multipartite symbiosis composed of termites, archaea, bacteria, and cellulolytic flagellates since its inception. Video Abstract.
Keywords: metagenom; Metagenome; Isoptera; Animals; Phylogeny; zvířata; Soil; půda; fylogeneze; střevní mikroflóra; Gastrointestinal Microbiome